'Eldum Unnyt': Treasure Spaces in Beowulf. - McNabb, Cameron (Neophilologus, 2011)
Treasure spaces in Beowulf serve as structural and thematic touchstones for Beowulf's fights with the Grendelkin and the dragon, and the locations of these fights-the mere, the barrow, and Heorot-are linked within the poem by their shared tomb-like structure and precious internal content. These three central locations are framed by two other treasure spaces in the poem-Scyld's ship burial and Beowulf's burial-at the beginning and end respectively, which also mirror the fight locations in structure and contents. Examined together, the parallels between these five enclosures create striking connections between their occupants: the Grendelkin, the dragon, Hrothgar, Scyld, and ultimately Beowulf. These parallels also attest thematically to the poem's overarching discussion on the transitory nature of material wealth, creating a network of associations between the spaces and their inhabitants. This framework complicates the veneration of the human heroes and demonstrates that the accumulation of earthly goods is ultimately as useless to a hero as to a monster.